PENGARUH MODEL PEMBELAJARAN ARIAS (ASSURANCE, RELEVANCE, INTEREST, ASSESSMENT, AND SATISFACTION) DALAM MENINGKATAN PRESTASI BELAJAR SISWA PADA MATERI IKATAN KOVALEN - Vivi, Vivi; Soleman, Pangoloan (Journal of Chemistry Education and Integration, 2024)
AbstractARIAS (Assurance, Relevance, Interest, Assessment, and Satisfaction) learning model is one of alternatives for teachers in conducting learning activities well because it is designed based on the learning theory. Learning achievement is a result that can be achieved by someone consciously or unconsciously with the hard work results of learning. This research aimed at analyzing ARIAS learning model in increasing student learning achievement on covalent bond lesson.  This research was conducted on covalent bond lesson in the academic year of 2022/2023 at state senior high school 12 Pekanbaru. Quasi-experimental method was used in this research.  The subjects of this research were two classes-experimental and control groups. The instruments used in this research were pretest-posttest, interview, and documentation to strengthen the data obtained. Based on the research findings, the posttest showed that the score of significance (2-tailed) 0 was lower than 0.05, so it showed that there was a significant difference between experimental and control groups. Besides, the N-Gain mean of student learning achievement in the experimental group was 11.43%, it was on high category, and the control group was 5.71% with moderate category. It could be concluded that learning with ARIAS learning model was effective to be used for student learning achievement.Keywords : ARIAS Model, Student Learning Achievement, Covalent Bond